2022
DOI: 10.3390/bios13010048
|View full text |Cite
|
Sign up to set email alerts
|

Improved Split TEV GPCR β-arrestin-2 Recruitment Assays via Systematic Analysis of Signal Peptide and β-arrestin Binding Motif Variants

Abstract: G protein-coupled receptors (GPCRs) are major disease-relevant drug targets; robust monitoring of their activities upon drug treatment is key to drug discovery. The split TEV cell-based assay technique monitors the interaction of an activated GPCR with β-arrestin-2 through TEV protein fragment complementation using a luminescent signal as the readout. In this work, split TEV GPCR β-arrestin-2 recruitment assays were optimized to monitor the endogenous ligand-induced activities of six GPCRs (DRD1, DRD2, HTR2A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The split TEV GPCR β-arrestin-2 recruitment assay relies on the functional complementation of TEV protease fragments (Figure 2F) [58,108]. It monitors the activation of a GPCR at the membrane through β-arrestin-2 recruitment.…”
Section: Split Tev Gpcr β-Arrestin-2 Recruitment Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The split TEV GPCR β-arrestin-2 recruitment assay relies on the functional complementation of TEV protease fragments (Figure 2F) [58,108]. It monitors the activation of a GPCR at the membrane through β-arrestin-2 recruitment.…”
Section: Split Tev Gpcr β-Arrestin-2 Recruitment Assaysmentioning
confidence: 99%
“…Split TEV GPCR assays were further optimized for transient transfection assays for use in HEK293, PC12, HeLa, and U-2 OS cells. These assays demonstrated that, with the exception of the DRD2 receptor, an N-terminal signal peptide (SP) and a vasopressin 2 receptor tail (V2R tail) at the C-terminus of the construct, common in similar assay systems, can be omitted in split TEV GPCR assays [108].…”
Section: Split Tev Gpcr β-Arrestin-2 Recruitment Assaysmentioning
confidence: 99%